Tuned In Emotion Regulation Program Using Music Listening: Effectiveness for Adolescents in Educational Settings - Dingle, Genevieve A. (Front Psychol, 2016)
This paper presents an effectiveness study of Tuned In, a novel emotion regulation intervention that uses participant selected music to evoke emotions in session and teaches participants emotional awareness and regulation skills. The group program content is informed by a two dimensional model of emotion (arousal, valence), along with music psychology theories about how music evokes emotional responses. The program has been evaluated in two samples of adolescents: 41 “at risk” adolescents (76% males; M(age) = 14.8 years) attending an educational re-engagement program and 216 students (100% females; M(age) = 13.6 years) attending a mainstream secondary school. Results showed significant pre- to post-program improvements in measures of emotion awareness, identification, and regulation (p < 0.01 to p = 0.06 in the smaller “at risk” sample and all p < 0.001 in the mainstream school sample). Participant ratings of engagement and likelihood of using the strategies learned in the program were high. Tuned In shows promise as a brief emotion regulation intervention for adolescents, and these findings extend an earlier study with young adults. Tuned In is a-theoretical in regard to psychotherapeutic approach and could be integrated with other program components as required.